Frequency of Metabolic Syndrome in Case with Ischemic Stroke - Hafiz Rahman, Kamran Ahmad, Junaid Raqib, Sultana Shaheen, Mohammad Imran Younus, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ischemic stroke is a leading cause of mortality and long-term disability worldwide, with a complex interplay of genetic and environmental risk factors. Among these, modifiable risk factors such as smoking, hypertension, dyslipidaemia, and diabetes have been well-established. In addition, Metabolic Syndrome (MetS), a cluster of conditions including obesity, insulin resistance, hypertension, elevated triglycerides, and reduced HDL cholesterol, significantly heightens the risk of ischemic stroke. Objective: This study aimed to assess the prevalence of Metabolic Syndrome in patients with ischemic stroke. Study Design: A cross-sectional observational study. Duration: 6-month period from May 16, 2019, to December 16, 2019. Methods: The study was conducted at the Department of Medicine, Lady Reading Hospital, Peshawar, involving 120 CT-confirmed ischemic stroke patients. These patients were evaluated for the presence of Metabolic Syndrome using standard diagnostic criteria. Results: The cohort had a mean age of 58.8 ± 9.8 years, with 64.2% being male. Metabolic Syndrome was identified in 55% of the study participants, highlighting its significant association with ischemic stroke. Conclusion: Metabolic Syndrome is a prevalent and substantial risk factor for ischemic stroke. This underscores the importance of early detection and management of MetS, as well as the need for community-based research to further explore its role in stroke pathogenesis. Keywords: Ischemic stroke, metabolic syndrome, obesity, hypertension, dyslipidaemia, smoking.